Review paperAntoni Rosner, the first associate professor of dermatology and venereology in Poland - Staszek, Dariusz; Jeśman, Czesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
The article presents an outline of the development of world and Polish dermatology. The author points out to the first descriptions of skin diseases by ancient and medieval medical luminaries. The outline of the Polish dermatology is based on examples of doctors living in the 16 th and 17 th centuries. The first clinics of skin and venereal diseases in Poland appeared, like in other European countries, in the second half of the 19 th century. Antoni Rosner, the first associate professor of clinical studies, greatly contributed to the development of this medical field. The description of his life and work is the background for the presentation of opening and developing the clinic of skin and venereal diseases in Krakow as well as the presentation of university curriculum at the Faculty of Medicine of the Jagiellonian University.